EKSISTENSI BUDAYA POLITIK DI INDONESIA : SEBUAH KAJIAN - Dr. Thomas Tokan Pureklolon (Jurnal Communitarian (Prodi Ilmu Politik), 2021)
AbstractPolitical culture is the pattern of individual behavior and orientation towards political life that is lived by the members of a system. Political culture is a citizen's perception that is actualized in the pattern of attitudes towards political problems and political events that occur so that it has an impact on the formation of the political structure and process of society and government because the political system is a relationship between humans which involves questions about rules, power, and also the authority they have. Thus the existence of political culture in Indonesia is very interesting to study. The method used in writing this journal is a qualitative method by conducting library research on political culture in Indonesia. The purpose of writing this journal is to describe the existence of political culture in Indonesia in accordance with the context, situation and objectives of political development in Indonesia.Key Word: Culture, government, politic, political culture, socialisation.AbstrakBudaya politik adalah pola tingkah laku indvidu dan orientasinya terhadap kehidupan politik yang dihayati oleh para anggota dari suatu sistem. Budaya politik merupakan persepssi warga negara yang diaktualisasikan dalam pola sikap terhadap masalah politik dan peristiwa politik yang terjadi sehingga berdampak terhadap pembentukan struktur dan proses politik. Masyarakat maupun pemerintahan karena sistem politik merupakan hubungan antar manusia yang menyangkut soal tentang aturan, kekuasaan, dan juga wewenang yang dimiliki. Dengan demikian eksistensi budaya politik di Indonesia sangat menarik untuk dikaji. Metode yang digunakan dalam penulisan jurnal ini adalah metode kualitatif dengan melakukan riset kepustakaan tentang budaya politik yang ada di Indonesia.Tujuan penulisan jurnal ini adalah untuk mendeskripsikan eksistensi budaya politik di Indonesia sesuai dengan konteks, situasi dan tujuan pembangunan politik di Indonesia. Kata Kunci : Budaya, pemerintahan, politik, politik budaya, sosialisasi